Pengaruh Variasi Slip Ratio Terhadap Keausan Lapisan Nikel Tungsten Pada Baja Karbon Sedang Akibat Beban Gelinding Luncur - Simatupang, Sesep Aditio; Widiyarta, I Made; Parwata, I Made (Teknik Desain Mekanika, 2017)
Abstrak Kereta api yang melintas diatas rel dengan beban maksimum per roda ke rel sebesar akan mengalami slip dan rolling antara roda dan rel ketika melakukan gerak awal, pengereman, pendakian, penikungan akan mempengaruhi keausan, sehingga mengurangi umur pemakaian rel. Untuk mempelajari hal ini dilakukan pengujian kontak twin disc, antara roda dan rel. Pengujian menggunakan baja karbon yang dilapisi Nikel Tungsten sebagai rel dan baja karbon sedang sebagai roda, yang diuji sebanyak 40.000 siklus putaran dengan rasio slip-roll sebesar 1%, 3%, dan 7%. Hasil uji menunjukkan, keausan akibat slip-roll ratio 1 % mencapai 0.583 mg, keausan akibat slip-roll ratio 3% mencapai 0.633 mg dan keausan akibat slip-roll ratio 7% mencapai 1.080 mg. Kata kunci : high slip-roll ratio, keausan, regangan geser, nikel, tungsten Abstract A Train passes on the rails with the maximum load per wheel to the rail of about 750 MPa will cause slip between the wheels and the rails when starting to move accelerating, braking, climbing and curving. The ratio of slip-rolling will affects the failure to wear at the rails material. To study the effect of slip roll ratio on the wear, rolling sliding contact test was conducted in the twin disc contact machine. Carbon steel with Nikel Tungsten coating was used as rail material and carbon steel as a wheel material. The test was performed with number of cycles of 40.000 cycles, with slip roll ratio of 1%, 3% and 7%. The results show, wear of coated material with 1% slip roll ratio is about 0,583 mg, slip-roll ratio 3% the wear is about 0.633 mg and slip-roll ratio 7% the wear is about 1.080 mg. Keywords: high slip-roll ratio, wear, shear strain, nickel, tungsten